Phenomenology of the Body (Leib) according to Edith Stein and Hermann Schmitz - Kammler, Steffen (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
Steffen Kammler carries out a detailed analysis of phenomenology of thebody contained in Edith Stein’s dissertation On the Problem of Empathy and Hermann Schmitz’s Philosphical System (System der Philosophie), highlighting similarities and deepdifferences in their views. The author shows the relevance of Edith Stein’s philosophical approach to these issues in dialogue with the newest trends in phenomenological studies and reveals the stimulating influence of Stein’s way of thinking about body (Leib) on German phenomenology in the second half of the twentieth century.